Tired heart and mute brain: handle with care - Koirala, E; Chapagain, A; Thapa, L; Gautam, M; Paudel, R; Pokhrel, BR; Rana, PVS (Journal of College of Medical Sciences-Nepal, 2012)
Managing a case of stroke is complex. Presence of variable sized brain infarct and heart failure is even more complex to manage. On top of this, presence of clot in the heart adds to confusion in medical management of stroke patients because of limited scientific evidences. With increasing number of stroke patients and improving diagnostic facility, it is interesting to find thrombus in ventricles of few of these patient, which otherwise were uncommon previously in our set up. We present a 64-year-old man, a case of ischemic stroke caused by left ventricular thrombus secondary to dilated cardiomyopathy and highlight the present recommendation to manage the condition. DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6714 Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 68-70